2012
DOI: 10.1111/j.1750-3841.2011.02539.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultivars, Culture Conditions, and Harvest Time Influence Phenolic and Ascorbic Acid Contents and Antioxidant Capacity of Strawberry (Fragaria x ananassa)

Abstract: This article compares the antioxidant capacity and the content in ascorbic acid and phenolic compounds of strawberries of different varieties and of fruits harvested from April to December at the same ripening stage. The importance of strawberry antioxidant capacity resides in its benefits for human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 41 publications
5
37
1
1
Order By: Relevance
“…The highest TPC were found in 'SJ0618' (420.6 mg 100 g in 'SJ081437'. The values obtained were within the range of previous findings by Pincemail et al (2012) for 12 strawberry cultivars but contrasted with the results reported by Khanizadeh et al (2008), which were much lower. The differences might be explained by different genotypes considered and production years.…”
Section: Resultscontrasting
confidence: 56%
“…The highest TPC were found in 'SJ0618' (420.6 mg 100 g in 'SJ081437'. The values obtained were within the range of previous findings by Pincemail et al (2012) for 12 strawberry cultivars but contrasted with the results reported by Khanizadeh et al (2008), which were much lower. The differences might be explained by different genotypes considered and production years.…”
Section: Resultscontrasting
confidence: 56%
“…In the light of the documented facts, it is confirmed that the season and cultivar affect the nutrient accumulation in fruits [7][8][9]. It is hypothesised that the harvesting season will also influence the physiological and functional qualities of strawberry fruits.…”
Section: Introductionmentioning
confidence: 74%
“…Plant materials contain different phenolic compounds with varied antioxidative properties (6,8,(10)(11)(12). Researchers have suggested that the poor correlation between the phenolic content and the antioxidant activity in nutrients may have resulted not only due to the presence of phenolic compounds with varied antioxidant activities, but also due to the other antioxidant compounds in the material like α-tocopherol, β-carotene, vitamin C, and selenium, etc (30,32,(54)(55).…”
Section: Correlation Between Total Phenolic Content and Antioxidant Amentioning
confidence: 99%
“…Studies have indicated a strong negative correlation between increased consumption of fruits and vegetables and risks of degenerative diseases like CHD, diabetes, Alzheimer's disease, cataract and some types of cancers (7)(8)(9). It has long been perceived that phenolic content is affected by environmental factors, e.g., pedoclimatic (soil, sunshine, rain), agronomic (conventional/hydroponic, organic, greenhouse farming methods), harvesting methods, and time, storage conditions and processing techniques (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%